Ion Transport Regulation by TRPV4 and TRPV1 in Lens and Ciliary Epithelium - Delamere, Nicholas A.; Shahidullah, Mohammad (Frontiers in Physiology, 2022)
Aside from a monolayer of epithelium at the anterior surface, the lens is formed by tightly compressed multilayers of fiber cells, most of which are highly differentiated and have a limited capacity for ion transport. Only the anterior epithelial layer has high Na,K-ATPase activity. Because the cells are extensively coupled, the lens resembles a syncytium and sodium-potassium homeostasis of the entire cell structure is largely dependent on the epithelium. Here we describe recent studies that suggest TRPV4 and TRPV1 channels activate signaling pathways that play an important role in matching epithelial ion transport activity with needs of the entire lens. A TRPV4 feedback loop senses swelling in the fiber mass and increases Na,K-ATPase activity to compensate. TRPV4 channel activation in the epithelium triggers ATP release by opening connexin hemichannels that stimulates purinergic receptors and results in the activation of Src family tyrosine kinases (SFKs) and SFK-dependent increase of Na,K-ATPase activity. A separate TRPV1 feedback loop senses shrinkage in the fiber mass and increases NKCC1 activity to compensate. TRPV1 activation causes calcium-dependent activation of a signaling cascade in the lens epithelium that involves PI3 kinase, ERK, Akt and WNK. TRPV4 and TRPV1 channels are also evident in the ciliary body where Na,K-ATPase is localized on one side of a bilayer in which two different cell types, nonpigmented and pigmented ciliary epithelium, function in a coordinated manner to secrete aqueous humor. TRPV4 and TRPV1 may have a role in maintenance of cell volume homeostasis as ions and water move through the bilayer.